Marco Tibayan Malone: capstone - Malone, Marco Tibayan, artist (Colorado State University. Libraries, 2021)
The artist's statement: In my work I always start off with a pen and a sketchbook instead of diving head first into using anything from the Adobe Creative Cloud. Technology is only as smart as you and creating a work without a solid idea and concrete steps is bound to lead to a lot more unintended mistakes and quite possibly a work that is unfinished or one that you are not proud of. Instead, I methodically pick out my approach for each project. What am I making for my client? What is their theme and brand? How can I differentiate their brand from others? Can I incorporate some of their previous ideas into the work I am producing for them? As I carefully navigate to the answers of these questions the work becomes more tangible due to understanding what is fundamentally required for the project. What I desire my work to be on the surface is professional and able to fulfill the requests of my clients. However, for myself I want my work to be reflective of my skill, my intricate and chaotic thought process, and incredibly detailed. For illustrations it could be maintaining a hyper realistic feel, having an ethereal atmosphere, or being able to captivate a person's attention with every miniscule feature that's in it. For UI's, websites, and publication design I want to maintain an immaculate structure and flow that's not only second nature to navigate but a beautiful visual journey for a person to experience whether they're looking at a poster or flipping through a book.
Colorado State University Art and Art History Department capstone project.
Capstone contains the artist's statement, a list of works, and images of works.
Keywords: graphic design